Plan de negocios para la creación de una empresa de empaques biodegradables (2023)
The establishment of Bioempac, which is dedicated to the production and processing of biodegradable packaging made of banana leaf, will be carried out in the environment-friendly city of Santa Marta (Magdalena Department Municipality). The aim of this organisation is to provide another packaging alternative for products, in a sustainable and environmentally friendly manner. The incorporación of this business model aims to provide a solution to the increase in the use of plastic packaging in foodstuffs, developing a new consumption habit, implemented through a functional value model structure in order to properly address this need. The present proposal outlines a mixed research typology, as the qualitative and quantitative model of recognition is implemented, together with elements such as primary and secondary sources, seeking overall analysis of the object of study and formulation. At the institutional level, the following alignment of organizations' management research is carried out.